PENERAPAN NILAI-NILAI PANCASILA DALAM PENDIDKAN - Ahmad Arif Fadilah; Alya Atsa; Siti Nur Anisa (Cahaya Ilmu Bangsa Institute, 2025)
As the basis of the Indonesian state, Pancasila has very important values ​​in the formation of national character, especially in the field of education. The application of Pancasila values ​​in education aims to instill attitudes and behavior that are in line with the noble principles contained in Pancasila, such as mutual cooperation, social justice and respect for human rights. In practice, these values ​​foster student character development, such as when teachers set an example, discuss relevant social issues, and involve students in social activities that foster a sense of financial support. This can be implemented through various focused teaching methods. This research aims to find out how the application of Pancasila values ​​in the school curriculum and learning process increases students' awareness of the importance of national values ​​and strengthens national identity. The results of the research show that the application of Pancasila in education can strengthen students' character and morals and encourage the creation of an educational environment. harmonious and inclusive. Effective implementation of Pancasila values ​​in education requires the involvement of all stakeholders, including government, educators and society, as well as the need to develop a young generation with noble character and integrity.